Extracellular vesicles in the retina - putative roles in physiology and disease - Kalargyrou, Aikaterini A.; Guilfoyle, Siobhan E.; Smith, Alexander J.; Ali, Robin R.; Pearson, Rachael A. (Frontiers in Molecular Neuroscience, 2023)
The retina encompasses a network of neurons, glia and epithelial and vascular endothelia cells, all coordinating visual function. Traditionally, molecular information exchange in this tissue was thought to be orchestrated by synapses and gap junctions. Recent findings have revealed that many cell types are able to package and share molecular information via extracellular vesicles (EVs) and the technological advancements in visualisation and tracking of these delicate nanostructures has shown that the role of EVs in cell communication is pleiotropic. EVs are released under physiological conditions by many cells but they are also released during various disease stages, potentially reflecting the health status of the cells in their cargo. Little is known about the physiological role of EV release in the retina. However, administration of exogenous EVs in vivo after injury suggest a neurotrophic role, whilst photoreceptor transplantation in early stages of retina degeneration, EVs may facilitate interactions between photoreceptors and Müller glia cells. In this review, we consider some of the proposed roles for EVs in retinal physiology and discuss current evidence regarding their potential impact on ocular therapies via gene or cell replacement strategies and direct intraocular administration in the diseased eye.